Blockchain Technology in the Digital Economy: Redefining Trust, Transparency, and Decentralization - Aminov, Sardor (TLEP – International Journal of Multidiscipline, 2024)
Blockchain technology, initially conceived as the foundation of Bitcoin, has evolved into a powerful tool reshaping various aspects of the global digital economy. Beyond cryptocurrencies, blockchain offers a decentralized, transparent, and secure method of conducting digital transactions and managing data. This paper explores the transformative potential of blockchain in the digital economy, analyzing its core features, implementation across industries, and challenges to mainstream adoption. Through examples in finance, supply chains, healthcare, governance, and digital identity, the paper illustrates how blockchain can foster a more secure and inclusive economic landscape. Despite technical and regulatory hurdles, blockchain’s decentralized architecture marks a pivotal shift from traditional centralized models, indicating a foundational role in the next phase of economic digitization.